Intersections of Sport and Society in Creative Writing
XV, 190 p. 3 illus., 1 illus. in color.
Keywords: This edited collection is positioned at the nexus of sports, society and creative writing. In its explorations of the intersections of sports writing, analysis of literary contributions and examinations of craft, it offers rare consideration of a rich diversity of form in narratives that occur in, and as creative practice. Included in the collection are dynamic academic investigations into football writing and poetry focused on community sporting activities in Afghanistan, to those addressing the intersections of writing and boxing in the reflexive reclamation of the post-trauma self, the absence of women in the rodeo and who and what is represented in our sports shelves. This book breaks new ground in approaches to sport’s role in creative writing and what creative writing can provide in furthering our understanding of sport in society. The works in this edited book draw on a diverse range of methods to interrogate the processes, concepts and liminal spaces through an intersectional array of voices, offering analysis and insight into the application of creative writing knowledge and practice in relation to sport and its impact on wider discipline discussion and research. It is relevant to students and scholars studying and researching creative writing, sports writing, sports studies, cultural studies and sports media studies.